Evaluating TRIZ Methodology in the Conceptual Design Phase of Industrial Products - Aditya Sahu (International Journal of Industrial and Product Design Engineering, 2025)
The Theory of Inventive Problem Solving (TRIZ) has emerged as a powerful systematic innovation methodology that enhances creativity and problem-solving efficiency in engineering design. This paper evaluates the application of TRIZ during the conceptual design phase of industrial products, where early-stage decisions critically influence functionality, cost, sustainability, and market competitiveness. TRIZ provides designers with structured tools—such as the 40 Inventive Principles, Contradiction Matrix, Su-Field Analysis, and Trends of Technological Evolution—that help identify and overcome technical contradictions without relying solely on intuitive brainstorming. By analyzing how these tools guide designers toward breakthrough concepts, this study highlights their relevance in accelerating ideation, reducing design risks, and fostering innovative alternatives. The evaluation draws on case studies from mechanical, electrical, and consumer product industries, demonstrating how TRIZ supports designers in systematically generating feasible solutions, minimizing trade-offs, and improving product performance. The methodology is particularly valuable for addressing complex engineering contradictions, enabling teams to foresee potential design limitations and integrate solutions aligned with technological evolution. Furthermore, TRIZ enhances collaborative decision-making by establishing a common innovation language among multidisciplinary teams. Overall, the study concludes that TRIZ significantly strengthens the conceptual design phase by promoting structured creativity, reducing development time, and improving solution novelty. Integrating TRIZ into early design workflows not only enhances product innovation potential but also contributes to sustainable and cost-effective engineering outcomes. This evaluation underscores the importance of adopting TRIZ as a strategic tool for industries seeking to remain competitive in an increasingly innovation-driven market.
Keywords: TRIZ methodology; conceptual design; contradiction matrix; engineering innovation; industrial product development; inventive problem solving; systematic design tools; technological evolution trends